Solomon Islands : First Review Under the Stand-by Credit Facility and Request for Modification of Performance Criteria and Re-phasing of Disbursements; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Solomon Islands. (IMF Staff Country Reports; Country Report, 2010)
Generally, macroeconomic performance has been as envisaged at the time of the program request. The near-term outlook has improved, despite uncertain global conditions. The new government of Solomon Islands remains committed to program targets and objectives agreed. The government's efforts in adhering to program fiscal targets are commendable, as the main anchor to macroeconomic stability. Excess liquidity in the banking system and commodity price pressures continue to pose inflation risks. Strong adherence to the program would help anchor macroeconomic policy and address structural weaknesses.